KONDISI PENCEMARAN PERAIRAN TELUK JAKARTA - Yudo, Satmoko (Jurnal Hidrosfir Indonesia, 2007)
Jakarta bay is a semi-closed waters located in north of Jakarta city. This waters has been getting pollutant such as domestic, organic and industrial waste, heavy metal or spill oil which trend to rise and it?s afraid to exceed its supportive capacity. To empty some rivers across Jakarta area into Jakarta bay, waters carry many pollutant. Every rives across Jakarta emty into Jakarta bay waters and it?s water quality is very effected by the condition of river water quality flowing to Jakarta bay. To know how bad the pollutan in Jakarta bay waters we have to check the condition of it?s water quality periodically. It is hope that the conclusion could be the ground to make preventions.Keywords: Jakarta Bay, water pollutant, waters quality database program development.